2002
DOI: 10.1046/j.1365-2249.2002.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofα1-proteinase inhibitor release by proinflammatory cytokines in human intestinal epithelial cells

Abstract: SUMMARYa1-Proteinase inhibitor (a1-PI) is the main serine proteinase inhibitor in human plasma. Apart from its synthesis in the liver, this anti-inflammatory protein is also synthesized by and excreted from human intestinal epithelial cells. Antiinflammatory actions of a1-PI are thought to be of relevance in the pathogenesis of inflammatory bowel disease. To investigate the role of macrophage-derived cytokines on a1-PI secretion from intestinal epithelial cells, we cultured Caco-2 cells until differentiation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Presumably, this increase results in the inhibition of neutrophil elastase, which breaks down connective tissue components causing tissue damage during inflammatory diseases. It has been suggested that extrahepatic α1-PI may also contribute locally, within specific organs, to the response initiated by an inflammatory or infectious process [14,41]. Our study extends this possibility to human pancreatic islets, raising the question of whether α1-PI is implicated in the protection of peripherally located islet cells, which are preferentially exposed to the autoimmune attacks leading to islet destruction.…”
Section: Discussionsupporting
confidence: 55%
“…Presumably, this increase results in the inhibition of neutrophil elastase, which breaks down connective tissue components causing tissue damage during inflammatory diseases. It has been suggested that extrahepatic α1-PI may also contribute locally, within specific organs, to the response initiated by an inflammatory or infectious process [14,41]. Our study extends this possibility to human pancreatic islets, raising the question of whether α1-PI is implicated in the protection of peripherally located islet cells, which are preferentially exposed to the autoimmune attacks leading to islet destruction.…”
Section: Discussionsupporting
confidence: 55%
“…Intestinal proteomics of NEC patients small intestine and colon could protect the intestinal mucosa from the ongoing inflammation damage, similar to its role in inflammatory bowel diseases (11). Two HSPs (HSPA5 and HSP27) were affected by the progression of NEC lesions in the small intestine as detected by proteomic analysis.…”
Section: Articlesmentioning
confidence: 75%
“…API has previously been shown to be synthesized by hepatocytes, macrophages, and intestinal epithelial cells (27), and gastric cancer has been reported to be associated with high levels of API in the gastric juice (28). It is also detectable in the feces of both healthy subjects and patients with inflammatory bowel disease (29), and in vitro evidence suggests that it is secreted in response to certain proinflammatory cytokines (30). There are also reports suggesting that high levels of API expression in sporadic colorectal tumors are associated with poor prognosis (31).…”
Section: Discussionmentioning
confidence: 99%